IN VITRO TESTING OF CLOVE EXTRACTS IN INHIBITING AND KILLING STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI - Nadia Dwi Rahmawati; Tri Nur Kristina; Endang Sri Lestari; Hardian Hardian (Jurnal Kedokteran Diponegoro, 2021)
Background: Diarrhea that could be caused by Staphylococcus aureus and Escherichia coli can be prevented by increasing hand hygiene using alcohol-based hand rub, but frequent use might cause skin irritation. Replacing alcohol with herbs could avoid this side effect. Cloves have been proved to have antibacterial properties. However, most researches used complex extraction methods that might not be applicable on a household scale.